2003
DOI: 10.1002/jso.10283
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients, antioxidants, and carcinoma of the gallbladder

Abstract: The data supports an association between lower levels of Se, Zn, vitamin E, and risk of carcinoma of the gallbladder and suggest that Cu/Zn ratio could be a useful parameter in evaluating the patients of carcinoma of the gallbladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…Statistically significant differences from the normal distribution of Fe, Cu, and Zn have been reported to occur in patients with various forms of cancers [10,11]. In some studies, the Cu/Zn ratio in serum samples has been utilized as chemoprophylaxis [12] and also as a way of evaluation and prognosis assessment in cancer patients [13][14][15]. To our knowledge, changes in the serum level of Fe, Cu, and Zn in bladder cancer patients has never been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically significant differences from the normal distribution of Fe, Cu, and Zn have been reported to occur in patients with various forms of cancers [10,11]. In some studies, the Cu/Zn ratio in serum samples has been utilized as chemoprophylaxis [12] and also as a way of evaluation and prognosis assessment in cancer patients [13][14][15]. To our knowledge, changes in the serum level of Fe, Cu, and Zn in bladder cancer patients has never been determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant difference was observed in tissue concentration of Mn, vitamin C, and vitamin E. Cu levels and Cu/Zn ratio showed a highly significant (P < 0.001) increase in serum, bile, and gallbladder tissue in GBC compared to the others. Their results support an association between lower levels of Se, Zn, vitamin E, and risk of carcinoma of the gallbladder and suggest that Cu/Zn ratio could be a useful parameter in evaluating the patients of carcinoma of the gallbladder [35].…”
Section: Discussionmentioning
confidence: 78%
“…Shukla et al evaluated the micronutrient deficiency in carcinoma of the gallbladder [35]. Selenium (Se), zinc (Zn), copper (Cu), manganese (Mn), ascorbic acid (vitamin C), and alphatocopherol (vitamin E) were estimated in the serum, bile, and gallbladder tissue of patients with GBC, cholelithiasis, and only in the serum of age-and sex-matched healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of TAC has been investigated for many cancers, no study has been published thus far (as shown by a search in PubMed) concerning the relationship between TAC levels and malignant biliary obstructions. The mean serum antioxidant levels, such as selenium, zinc, manganese, vitamin E, and vitamin C, were found to be significantly lower in gallbladder cancer patients as compared to patients with gallstones as well as healthy subjects (p<0.001) (51). Moreover, the roles of chronic inflammation and oxidative stress have been shown in CCA (52).…”
Section: Original Articlementioning
confidence: 99%